Foreign Direct Investment and Knowledge Diffusion in Poor Locations - Girum Abebe; Margaret McMillan; Michel Serafinelli (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
We use a plant level survey to identify interactions between domestic plants and foreign direct investment (FDI) in Ethiopia's manufacturing sector. Almost one third of Ethiopian plants report being linked to FDI through labor sharing, forward and backward linkages and competition in input and output markets. Domestic plant managers report that through these linkages with FDI, they learn about production processes, managerial and organizational practices and exporting. We quantify the spillovers from FDI at the local level by comparing changes in total factor productivity (TFP) among domestic plants in districts where a large greenfield foreign plant produced and districts where FDI in the same industry and around the same time was licensed but not yet operational. Over the four years starting with the year of the FDI opening, the TFP of domestic plants is 11 percent higher in treated districts, employment in these domestic plants increases and new domestic plants open.
Keywords: F21; R10; D24; 330; Foreign Direct Investment; productivity; localized knowledge spillovers; plant-to-plant labor mobility